Discriminating entrepreneurship intentions: empirical study of young Indian IT professionals. (2016) - Mukundan, Rajeev; Thomas, Sam
The Indian IT industry has contributed significantly to its economic growth in the last two decades. Understanding the drivers of entrepreneurship intention (EI) among young professionals can help advance the entrepreneurial activity in the industry, and frame regulatory/academic policies. 184 new-to-the-corporate IT professionals and 30 real entrepreneurs, all aged in their 20s and mostly in early 20s, were studied to understand their EI and its drivers. Applying theory of planned behaviour, attitude towards entrepreneurship (ATE), subjective norms (SNs) and perceived behavioural control (PBC) were considered as the antecedents of EI. The sample was classified into three categories: non-entrepreneurs with low EI, non-entrepreneurs with high EI, and real entrepreneurs. Discriminant analysis was done to validate this classification and the relationship between EI and its three antecedents. ATE was the strongest predictor of entrepreneurial behaviour. The study extends the existing literature on EI by providing the Indian IT industry context and by adding real entrepreneurs in scope.